2018
DOI: 10.1016/j.cjtee.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of pediatric ocular trauma in a tertiary hospital of northern India

Abstract: PurposeOcular trauma is one of the most common causes of acquired blindness in children. It measures about 8%-14% of total childhood injuries. This study aims to determine the epidemiological profile of ocular trauma in the pediatric age group attending a tertiary hospital in northern India.MethodsA retrospective study was conducted in our hospital between June 2014 to July 2015 and all the children aged 0-16 years presenting with ocular trauma in eye outpatient department and emergency were enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 18 publications
11
41
3
1
Order By: Relevance
“…Open globe injuries present more potential for poor vision than the closed globe injuries. 3,11,[21][22][23][24][25][26][27][28] In our study, six patients presented with NPL, and five remained NPL after surgical repair of the perforation site. Poor prognosis in these patients could be due to repeated surgical interventions, development of secondary glaucoma, and/or endophthalmitis.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Open globe injuries present more potential for poor vision than the closed globe injuries. 3,11,[21][22][23][24][25][26][27][28] In our study, six patients presented with NPL, and five remained NPL after surgical repair of the perforation site. Poor prognosis in these patients could be due to repeated surgical interventions, development of secondary glaucoma, and/or endophthalmitis.…”
Section: Discussionmentioning
confidence: 63%
“…This observation correlates with Qayum et al, who also found that sports-related injuries are common with respect to closed globe injuries, and wooden stick injuries were found in open globe. 28 Most of the studies demonstrate the wooden stick as a common cause of injury. 11,21,26,29 Availability of wooden material in the vicinity of the house could be the reason for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 249 patients, with a median (range) follow-up period of 7.8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) months, were included in this study. Two hundred and twenty-seven (91.2%) were males with an age range from 2 to 79 years, while 22 (8.8%) were females with an age range from 1 to 76 years.…”
Section: Resultsmentioning
confidence: 99%
“…There are about 1.6 million people blind due to eye injuries; in addition to this, 2.3 million are having low vision bilaterally and 19 million represent unilateral visual loss, making eye trauma the most common etiology of unilateral blindness 3,4 . Eye injuries measure about 8%~14% of the total childhood injuries 5,6 . Previous studies showed higher incidence of eye injuries in males 5,7,8 .…”
Section: Discussionmentioning
confidence: 99%